High-temperature Creep Behavior of Oxide Dispersion Strengthened HT9 Steel at 650 ℃ Based on Small Sample Testing - CHENG Shuo1, LI Shijiang1, GONG Aoxiang1, ZHAO Lei2, TONG Zhenfeng1, (Yuanzineng kexue jishu)
One of the most popular materials for advanced nuclear energy systems is oxide dispersion strengthened (ODS) steel, which has been widely adopted as a candidate material for advanced nuclear energy systems due to its high-temperature mechanical properties and resistance to irradiation. Because of the powder metallurgy preparation process used in the preparation of ODS steels, the material is mostly of fine or ultra-fine crystalline organization. The mechanism of high-temperature creep behavior of this type of such fine-crystalline materials is more complex, and there are few researches on the mechanistic changes in the creep deformation process. In addition, there is a lack of in-depth understanding of the effects on the creep behavior of grain scale and diffusely reinforced particles. In this paper, the oxide dispersion strengthened steel HT9-ODS and the reference HT9 steel were taken as the objects of study, and they were prepared into small-sized samples for high-temperature creep experiments. The experimental temperature was selected as the typical fast neutron reactor service temperature of 650 ℃, and the stress interval was 80-180 MPa. The creep fracture morphology and microstructure of the samples were characterized and tested by using micro-scale characterization techniques. By comparing and analyzing the high-temperature creep strain curves of reference HT9 steel and oxide dispersion strengthened steel HT9-ODS, the creep behavior of HT9-ODS steel at high temperatures was investigated. The results show that when the stress is higher than 100 MPa, grain boundary sliding plays a dominant role in the creep deformation process, which promotes crack initiation and aggregation, and fracture occurs in a shorter time for both HT9-ODS steel and the reference HT9 steel. The pinning of dislocations by oxide dispersed particles leads to the concentration of stress at grain boundaries, which accelerates the fracture of HT9-ODS steel, making the creep life of HT9-ODS steel shorter than that of reference HT9 steel. As the stress is reduced to 80 MPa, the grain boundary sliding effect decreases, and the creep deformation of reference HT9 and HT9-ODS steels is mainly the result of the synergistic effect of dislocation creep and diffusion creep. In this case, the dislocations of the reference HT9 steel cross the second phase particles in a climbing manner and the dislocations of the HT9-ODS steel bypass the second phase particles according to the Orowan mechanism. The creep life of HT9-ODS steel is much longer than that of reference HT9 steel due to the oxide dispersed particles hindering the dislocation motion.